Screening Study of the Anxiolytic Activity of New Triazole Compounds - S.D. Rakhimboev; Z.I. Sanoev; S.Z. Rashidov; I.T. Abdinazarov; T.T. Khamroev; D.S. Ismailova; B.J.Elmuradov (Zien Journals, 2022)
The article presents data on the study of the anxiolytic activity of compounds representing new triazole derivatives – combinations of two privileged structures. At the "Raised Cruciform labyrinth" installation, such indicators of the studied compounds, the time of exit into the open sleeve, the number of exits and the total time spent in it were studied that the D-389 compounds are not inferior to the comparison drug, which indicates the presence of high anxiolytic activity.
Keywords: triazole compounds; seduxene; anxiolytic; raised cruciform labyrinth